Cote d'Ivoire : Staff Report for the 2018 Article IV Consultation and Third Reviews Under the Arrangement Under the Extended Credit Facility and Extended Arrangement Under the Extended Fund Facility, and Request for Modification of a Performance Criterion. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2018)
This IMF Staff Report highlights that the robust economic growth in Cote d'Ivoire is projected to continue in 2018. The inflation remains subdued. The program aims to achieve a sustainable balance of payments position, foster inclusive growth and poverty reduction, and create fiscal space for investing in priority infrastructure and social projects. Strong economic performance since 2012, with average annual growth of 9 percent, reflected the economic recovery following political normalization, improved business environment, strong program of reforms, and supportive fiscal policy. A key policy challenge is to sustain robust growth and make it more inclusive and private sector-driven. Robust medium-term growth is expected to be supported by domestic demand.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet